2011
DOI: 10.1103/physrevb.84.100504
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inhomogeneity and planar symmetry breaking of the lattice incommensurate supermodulation in the high-temperature superconductor Bi2Sr2CaCu

Abstract: One of the emerging common features of high temperature superconductors (HTSs) is the intrinsic lattice inhomogeneity [1-4] but it remains practically unknown because of the lack of methods probing both the k-space and the real space from nano-scale to micronscale. The intrinsic lattice inhomogeneity is related with the co-existence of two or more electronic components showing a nanoscale phase separation in the normal phase [3][4]. In fact two strongly correlated electronic components at the Fermi level are e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 62 publications
4
59
0
Order By: Relevance
“…[83][84][85] and now it is used in a more general context. 86,87 We believe that the word "arrested" is more adequate here and prefer to use it.…”
Section: Poles Of Thementioning
confidence: 99%
“…[83][84][85] and now it is used in a more general context. 86,87 We believe that the word "arrested" is more adequate here and prefer to use it.…”
Section: Poles Of Thementioning
confidence: 99%
“…In several doped cuprates, they yield a characteristic incommensurate superstructure with the specific wavevector 0.21bà (38)(39)(40)(41)(42)(43)(44)(45)(46). Recent scanning tunneling microscopy work has clearly shown that the local lattice distortions of the CuO 2 plane induce a spatial modulation of the gap (11).…”
mentioning
confidence: 99%
“…Recent scanning tunneling microscopy work has clearly shown that the local lattice distortions of the CuO 2 plane induce a spatial modulation of the gap (11). The incommensurately modulated local lattice distortions (LLD) are a type of static charge density wave (CDW) established in nanoscale regions, whose size is indicated by the widths of diffuse X-ray satellites (37)(38)(39)(40)(41)(42)(43)(44)(45). Here we use X-ray microscopy to show that for the cuprate superconductor, La 2 CuO 4þy , the dominant features of the embedding glue regions, where interstitials are disordered, are optimally ordered arrays of tilt defects of the copper-centered oxygen plaquets, which are the fundamental building blocks of the cuprates.…”
mentioning
confidence: 99%
“…More specifically, for example, microbeams have been used for mapping weak diffuse scattering in the real space in Scanning micro X Ray Diffraction (SµXRD) measurements. The collected data, treated by spatial statistical tools, have shown the formation of fractal patterns of interstitial oxygens ordered domains in LCO [21], intrinsic phase separation in doped iron-chalcogenides [22,23] and planar symmetry breaking in Bismuthates [24]. More recently, it's has been demonstrated that the quenched disorder due to dopants is spatially anticorrelated with electronic textures and/or local lattice distortions in Hg1201 [12,13] and LCO [25].…”
mentioning
confidence: 99%